Alpha-Blockers As Colorectal Cancer Chemopreventive: Findings from a Case–Control Study, Human Cell Cultures, and In Vivo Preclinical Testing - Suzuki, Nobumi; Niikura, Ryota; Ihara, Sozaburo; Hikiba, Yohko; Kinoshita, Hiroto; Higashishima, Naoko; Hayakawa, Yoku; Yamada, Atsuo; Hirata, Yoshihiro; Nakata, Ryo; Okamoto, Makoto; Sano, Munetaka; et al. (Cancer prevention research (Philadelphia, Pa.), 2019)
A retrospective case–controlled analysis was performed to identify drug candidates in the current use that may prevent colorectal cancer, outside of aspirin. A total of 37,510 patients aged ≥20 years were assessed to identify subjects who had been diagnosed with colorectal cancer by colonoscopy without a previous diagnosis of colorectal cancer, inflammatory bowel disease (IBD), or gastrointestinal symptoms; 1,560 patients were identified who were diagnosed with colorectal cancer by colonoscopy. The patients with colorectal cancer were matched with 1,560 age, gender, family history of colorectal cancer and comorbidity-matched control patients who were not diagnosed with colorectal cancer at colonoscopy. The medication histories were compared between the two groups. Next, candidate drugs that were more frequently used by the control patients were selected and their effects on human colorectal cancer cell lines in vitro and an inflammation-induced mouse model of colorectal cancer were tested. Putative colorectal cancer preventative agents were identified, including aspirin, vitamin D, vitamin B, vitamin C, vitamin E, xanthine oxidase inhibitor, alpha-blockers, angiotensin receptor blocker, nateglinide, probiotics, thienopyridine, folic acid, nitrovasodilators, bisphosphonates, calcium channel blockers, steroids, and statins (P < 0.05). Alpha-blockers and xanthine oxidase inhibitors were selected for further study because these agents have not been analyzed previously as factors that may affect colorectal cancer outcomes. In vitro doxazosin (alpha-blocker), but not febuxostat (xanthine oxidase inhibitor), suppressed the proliferation of human colorectal cancer cells. Doxazosin also decreased tumorigenesis in an AOM/DSS mouse colorectal cancer model. Alpha-blockers may prevent colorectal cancer.